POLITIK HUKUM INVESTASI DALAM PEMBANGUNAN IBU KOTA BARU DITINJAU DARI UNDANG-UNDANG NO 3 TAHUN 2022 - Krisna Mukti Pradana; Faisal Samsudin; Bhim Prakoso (Jurnal Cakrawala Ilmiah, 2023)
Law Number 3 of 2022 concerning the Capital City (IKN Law) has become the focus of debate due to the lack of public participation and the brief formation process. This study, utilizing a normative juridical method, assesses the legal politics within the IKN Law through a legal and case-based approach. The research results indicate that the involved legal political dynamics have not fully reflected the needs of the society, evident from a superficial analysis of the academic text and indications of formal and material flaws due to hastiness. Remedial measures are necessary, such as fostering more active public participation, conducting in-depth analyses of societal needs, addressing formal and material flaws, enhancing transparency, adjusting the formation timeline, collaborating with stakeholders, periodic evaluations, and educational campaigns. Thus, it is expected that the IKN Law can be more effective, represent the interests of the public, and provide a solid legal foundation for the development of the new Capital City.